Knowledge and Attitudes about HIV/AIDS among Homoeopathic Practitioners and Educators in India - Nyamathi, Adeline (Oxford University Press, 2008)
This study is designed to assess AIDS knowledge among Homeopathy educators and physicians in India, which has not been evaluated previously. India now has the largest number of HIV infected persons worldwide, with an estimated cumulative 5.1 million infections. Homeopathy is the dominant system among the nationally-recognized alternative or complementary systems of medicine, which collectively provide health care to around 600 million people in India. Homeopathy, with its holistic and patient-centered approach, has a wide reach to people at risk of contracting human immunodeficiency virus (HIV). Participants were 68 homeopathy physicians (34 educators and 34 practitioners) who completed a CDC questionnaire measuring HIV/AIDS Knowledge regarding AIDS. This study reports the current level of knowledge of, and attitudes about, HIV/AIDS among homeopathy educators and practitioners. These findings will assist in the development of an education module to equip homeopathic health care personnel to impart accurate AIDS information and prevention counseling to their patients in an efficient manner.